2020
DOI: 10.1016/j.conctc.2019.100508
|View full text |Cite
|
Sign up to set email alerts
|

The iReAct study – A biopsychosocial analysis of the individual response to physical activity

Abstract: BackgroundPhysical activity is a substantial promoter for health and well-being. Yet, while an increasing number of studies shows that the responsiveness to physical activity is highly individual, most studies focus this issue from only one perspective and neglect other contributing aspects. In reference to a biopsychosocial framework, the goal of our study is to examine how physically inactive individuals respond to two distinct standardized endurance trainings on various levels. Based on an assessment of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 87 publications
(72 reference statements)
1
25
0
Order By: Relevance
“…The results of the present study are completely in the line of theoretical assumptions of the theory of reasoned action (Adams & Shambaugh, 2019).On the other hand, Attitude means the overall feeling of like or dislike toward any given PA behavior (Ajzen, 2011;Thiel et al, 2020). In Carvalho's study, people who did not have a good attitude toward physical activity prevented their physical activity (Carvalho et al, 2017).…”
Section: Discussionsupporting
confidence: 66%
“…The results of the present study are completely in the line of theoretical assumptions of the theory of reasoned action (Adams & Shambaugh, 2019).On the other hand, Attitude means the overall feeling of like or dislike toward any given PA behavior (Ajzen, 2011;Thiel et al, 2020). In Carvalho's study, people who did not have a good attitude toward physical activity prevented their physical activity (Carvalho et al, 2017).…”
Section: Discussionsupporting
confidence: 66%
“…The iReAct (Individual Response to Physical Activity) study was an interdisciplinary research project that investigated the physiological, affective, and cognitive responses to HIIT and MICT at the individual level (Thiel et al 2020 ). Information pertaining the current study is presented below.…”
Section: Methodsmentioning
confidence: 99%
“…Information pertaining the current study is presented below. Further details on the clinical trial can be found elsewhere (Thiel et al 2020 ). In the present manuscript, we analyzed the effects of the first training period only.…”
Section: Methodsmentioning
confidence: 99%
“…The current study was part of a large research project named iReAct (Individual Response to Physical Activity). The iRe-Act study was an interdisciplinary research project which investigated the physiological, affective, and cognitive responses to HIIT and MICT at the individual level (Thiel et al, 2020). We used a two-period sequential training intervention, where previously sedentary healthy participants were randomly assigned to 6 weeks of HIIT followed by 6 weeks of MICT exercise training or vice-versa.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that even though the phase of the menstrual cycle status within which testing occurred was not controlled in this study, this was not a major consideration in our design as there is compelling evidence showing that the phase of the menstrual cycle does not seem to have an effect on submaximal and maximal outcomes, as well as on microvascular measures (Mattu et al, 2020;Williams et al, 2020). Further inclusion criteria may be found elsewhere (Thiel et al, 2020).…”
Section: Recruitment and Inclusion Criteriamentioning
confidence: 99%